Herding cats : a strategic approach to social media marketing - Rohm, Andrew; Weiss, Michael (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
One of the top marketing challenges that marketing managers and executives face today is to better understand social media and its promise as a marketing platform. The social media ecosystem, including traditional platforms such as Facebook and Twitter and upstarts such as Instagram and Snapchat, have evolved significantly over the past 10 years, so much so that keeping pace with the latest social media platforms can seem like herding cats. To help you craft a more strategic approach to your social media efforts, we provide a timeless perspective on how to create, manage, and measure social media content. We simplify the concept of branding and advertising fueled by social media to one that focuses on understanding your why (Chapter 1); fostering customer engagement (Chapter 2) through crafting your organization's unique story (Chapter 3); telling the story strategically via social media channels (Chapter 4); organizing for social media and managing, monitoring, and measuring your social media efforts as well as developing guidelines and governance policies for executing your social media strategy (Chapter 5); identifying key metrics and measuring performance through analytics (Chapter 6); learning from several social media best practice examples (Chapter 7); and understanding the extent of change brought on by digital and social media related to how you engage your customers (Chapter 8). This book is intended to provide the reader--whether an upper level undergraduate or MBA student, social media manager, brand manager, small business owner, corporate executive, or simply someone who wishes to better understand the intersection of business and social media-- important perspectives and frameworks on developing and managing an effective social media strategy.
1. Who are you and why should we care? -- 2. Customer engagement -- 3. It's story time! -- 4. Creating your content -- 5. If content is king, then distribution is queen: how to manage your story across social media -- 6. Social media analytics: CSI meets advertising -- 7. Social media marketing best practices -- 8. The new front line -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 91-93) and index.
Title from PDF title page (viewed on August 4, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Internet advertising; Social media; advertising; analytics; branding; brand storytelling; customer engagement; customer relationship management; digital marketing; metrics; social media marketing; Electronic books